Improved Survival with Therapeutic Hypothermia after Cardiac Arrest with Cold Saline and Surfacing Cooling: Keep It Simple - Granja, Cristina; Ferreira, Pedro; Ribeiro, Orquídea; Pina, João (Emergency Medicine International, 2011)
Aim. To evaluate whether the introduction of a therapeutic hypothermia (TH) protocol consisting of cold saline infusion and surface cooling would be effective in targeting mild therapeutic hypothermia (32–34∘C). Additionally, to evaluate if TH would improve survival after cardiac arrest. Design. Before-after design. Setting. General Intensive Care Unit (ICU) at an urban general hospital with 470 beds. Patients and Methods. Patients admitted in the ICU after cardiac arrest between 2004 and 2009 were included. Effectiveness of the TH protocol to achieve the targeted temperature was evaluated. Hospital mortality was compared before (October 2004–March 2006) and after (April 2006–September 2009) the protocol implementation. Results. Hundred and thirty patients were included, 75 patients were not submitted to TH (before TH group), and 55 were submitted to TH (TH group). There were no significant differences concerning baseline, ICU, and cardiac arrest characteristics between both groups. There was a significant reduction in hospital mortality from 61% (n=46) in the before TH group to 40% (n=22) in the TH group. Conclusion. Our protocol consisting of cold saline infusion and surface cooling might be effective in inducing and maintaining mild therapeutic hypothermia. TH achieved with this protocol was associated with a significant reduction in hospital mortality.